DRY NEEDLING VERSUS INSTRUMENT ASSISTED SOFT TISSUE MOBILIZATION FOR THE TREATMENT OF MYOFASCIAL PAIN SYNDROME OF HAMSTRINGS MUSCLES: A PILOT STUDY (Cuestiones de Fisioterapia, 2020)
Introduction: Dry Needling (DN) is a treatment technique that is minimally invasive, effective and low risk for treating trigger points. Objectives: The aim of this study was to evaluate the effectiveness of DN technique carried out on biceps femoris compared to the Instrument Assisted Soft Tissue Mobilization (IASTM) technique in subjects with Myofascial Pain Syndrome (MPS). Material and method: a randomized clinical trial was conducted on 16 sub-jects divided into two experimental groups (GE1: n = 8 and GE2: n = 8). DN was applied to GE1 and IASTM to GE2.or three weeks, this trial measured the active and passive range of motion (ROM) of knee and hip and the pressure pain threshold (PPT) on myofascial trigger points (MTrPs) before and after the treatment. Two separate treatment sessions were carried out for 7 days and a follow-up without intervention in the third week. Results: there was a statistically significant increase (p < 0.01) in the pressure pain threshold within the groups, but no statistically significant differences (p > 0.05) were found between groups. Conclusions: dry needling and IASTM technique seem to be equally effective in increasing the pressure pain threshold of the hamstring trigger points.